Developing a Muslim response to the western criticism of the Prophet Muhammad - Bahari, Che Amnah; Abdullah, Fatimah (International Islamic University (IIU), 2010)
The Western approaches towards the Prophethood of Mu╒ammad (peace be on him), from the early Middle Ages to the present time, have been critical and hostile. He was depicted as a demon or a Christian heretic or a madman. Those critics however changed their tone particularly with the downfall of the Ottoman Empire. This change of Western writers’ mode towards the Prophet Mu╒ammad (peace be on him), however, was short lived. The tradition of hurling a variety of criticisms and hostilities against the Prophet (peace be on him) reemerged towards the end of the cold war and more particularly after September 11, 2001. These criticisms reemerged in all kinds and forms, to name a few, in academic writings, fiction, cartoons, films and toy products. This article is an attempt to study the Western criticisms hurled towards Mu╒ammad (peace be on him) discussing the issues of his Prophethood, his position as the Messenger to mankind, the second part of Shah┐dah and the finality of his Prophethood. These issues are treated here in the context of developing a Muslim response in refuting the Western criticisms, in the light of teachings of the Qur’┐n and the Sunnah of the Prophet Mu╒ammad (peace be on him) along with the deliberations of Islamic scholars.